Review on Portable-Powered Lower Limb Exoskeletons - Chunyu Jiang; Junlong Xiao; Haochen Wei; Michael Yu Wang; Chao Chen (Sensors)
Advancements in science and technology have driven the growing use of robots in daily life, with Portable-Powered Lower Limb Exoskeletons (PPLLEs) emerging as a key innovation. The selection of mechanisms, control strategies, and sensors directly influences the overall performance of the exoskeletons, making it a crucial consideration for research and development. This review examines the current state of PPLLE research, focusing on the aspects of mechanisms, control strategies, and sensors. We discuss the current research status of various technologies, their technological compatibility, and respective benefits comprehensively. Key findings highlight effective designs and strategies, as well as future challenges and opportunities. Finally, we summarize the overall status of PPLLE research and attempt to shed light on the future potential directions of research and development.